Dinamika Pewahyuan Al-Qur’an dan Rahasia Dibalik Sabʿatu Aḥruf - Ummi Fadhilah; Yamin Yamin; Andi Miswar (LPPM IAIN Sorong, 2026)
The study aims to explain the stages of the Qur’anic revelation, the parties involved at each stage, and the forms and mechanisms of its transmission. It also clarifies the meaning of sabʿatu aḥrūf and its difference from qirā’ah sab’ah. This research uses a qualitative library method. The findings show that most scholars hold that the Qur’an was revealed all at once from Lauḥ al-Maḥfūẓ to Bait al-‘Izzah on the night of Lailatul Qadr, then revealed gradually to the Messenger over about twenty-three years. The involvement of the angel Jibril in the first stage is not supported by definitive evidence, so this stage is attributed directly to Allah. Jibril’s role is firmly established in conveying revelation to the Messenger. Revelation occurred through true dreams and angelic mediation. Sabʿatu aḥrūf refers to seven Arabic varieties conveying one meaning and differs from qirā’ah sab’ah, which emerged after the Prophet’s death previously